Retelling strategy and reading comprehension, among eighth-grade students at a public institution in Loja, during the 2022-2023 school year. - Pinta Ochoa, Diana Cristina (2023)
Reading comprehension is a fundamental aspect in the teaching and learning of the English language since it enhances critical thinking, communication, and knowledge acquisition. This research aimed to improve reading comprehension through the application of the retelling strategy, among eighth-grade students at a public institution in Loja, during the 2022- 2023 school year. Based on this objective, two specific objectives were established: to validate the effectiveness of the retelling strategy in the improvement of reading comprehension and to describe the students' perceptions about its use. To achieve these objectives, a mixed-method with an action research design was employed involving 25 eighth-grade students at a public institution in Loja-Ecuador. Quantitative and qualitative data were collected through a pretest, posttest, questionnaire, and field notes. The pretest and posttest focused on measuring students' reading comprehension skills, including identifying the main idea and supporting details, inferring, sequencing and vocabulary use. On the other hand, the questionnaire and field notes explore students' perceptions of the use of the retelling strategy. These data were interpreted using descriptive statistics and analyzed using thematic analysis. From the results obtained in the tests, it was evident that the students had a slight improvement in their reading comprehension skills. In addition, the results of the questionnaire showed that the application of retelling had a positive impact on the students since this strategy fostered students' engagement, interaction, and socialization in the classroom. Consequently, the researcher concluded that retelling was an effective strategy that had a positive influence on the improvement of students' reading comprehension skills. Keywords: language acquisition, professional development, reading comprehension strategies, critical thinking